The Influence of Orthodontic Care on Periodontal Health in Individuals with Temporo-Mandibular Disorders (TMDS) - Abid Kanju, Syeda Midhat Batool, Taimur Khan, Nousheen Khan, Marij Hameed, Samar Nazir, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: The cause-and-effect link between orthodontic treatment and malocclusion and temporomandibular disorders (TMDs) has evolved into a hypothesis with insufficient data. Objective: Aim of this study is to determine the outcomes of orthodontic care on periodontal health individuals with temporo-mandibular disorders (TMDs). Methods: Total 190 patients of temporo-mandibular disorders were presented in this study. After getting informed written consent detailed demographics of enrolled cases were recorded. Patients were categorized in two groups, group I received orthodontic treatment among 95 cases and 95 cases of group II was without orthodontic treatment. In terms of their history of trauma, bruxism, forceful tooth brushing, degree of oral cleanliness, discomfort and muscle tenderness ratings, and subjective sleep quality, patients who received orthodontic treatment were compared to those who did not. Results: There was majority males 110 (57.9%) and 80 (42.1%) were females. Patients mean age was 24.64±13.72 years. In group I 63 cases received mandibular orthodontic treatment and 32 cases received maxillary orthodontic treatment. When compared to group II, we found that orthodontic treatment was linked to better oral hygiene than bad, less sore muscles, and lower (better) Pittsburgh Sleep Quality Index (PSQI) ratings (p <0.002). Conclusion: We observed that orthodontic treatment is not linked with TMDs, even after accounting for confounding and/or mediating variables such as trauma history, parafunctional behaviors and bruxism, pain scores, muscular tenderness scores, and subjective sleep quality. Keywords: Orthodontic treatment, TMDs, Periodontal health